A Comparative Analysis of EU and U.S. Capital Markets and Their Impact on Competitiveness - Palivec, Adam; Kopkáně, Heřman; Ali, Tanweer; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
The thesis compares EU and U.S. capital markets to assess how market fragmentation, the absence of a unified EU securities regulator, reduced IPO attractiveness, and politically rooted integration barriers affect the EU’s global competitiveness. By analysing aggregate data, consulting policy documents (Draghi Report, CMU initiatives), reviewing academic literature, and conducting expert interviews, the thesis identifies core obstacles to deeper market integration. The findings will bring realistic policy recommendations for EU institutions and offer strategic guidance for companies, supporting the development of a more integrated, investor-friendly, and globally competitive European economy.
Vedoucí práce: Heřman Kopkáně
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses